A dermocosmetic containing bakuchiol, Ginkgo biloba extract and mannitol improves the efficacy of adapalene in patients with acne vulgaris: result from a controlled randomized trial - Poláková K; Fauger A; Sayag M; Jourdan E (Dove Medical Press, 2015)
Katarína Poláková,1 Aurélie Fauger,2 Michèle Sayag,2 Eric Jourdan2 1Saint Elisabeth´s Oncological Institute, Bratislava, Slovakia; 2Laboratoire Bioderma, Lyon, France Background: Acne vulgaris is an inflammatory disorder of the pilosebaceous unit. Aim: To confirm that BGM (bakuchiol, Ginkgo biloba extract, and mannitol) complex increases the established clinical efficacy of adapalene 0.1% gel in patients with acne. Methods: A clinical trial was conducted in acne patients. A total of 111 subjects received adapalene 0.1% gel and BGM complex or vehicle cream for 2 months. Assessments comprised Investigator Global Assessment (IGA), global efficacy, seborrhea intensity, inflammatory and non-inflammatory lesions, and subject perception, as well as overall safety and local tolerance and quality of life. Results: At the end of the trial, inflammatory and non-inflammatory lesions, IGA, global efficacy, and seborrhea intensity had significantly improved in both treatment groups. Differences were statistically significant (P<0.05) in favor of BGM complex for inflammatory lesions as well as IGA and seborrhea intensity. Global efficacy assessments and subject perception confirmed the superiority of BGM complex-including treatment over the comparative combination. Quality of life had improved more with the active combination than with the vehicle combination. In the active group, four subjects had to interrupt temporarily BGM complex and 12 adapalene compared to seven subjects interrupting the vehicle and eleven adapalene in the vehicle group. One subject withdrew from the trial due to an allergy to adapalene. The majority of all events were mild. Conclusion: BGM complex improves the treatment outcome of adapalene 0.1% gel in patients with acne vulgaris. Overall, safety and local tolerance of BGM complex were good. Keywords: adapalene, acne vulgaris, bakuchiol, BGM complex, P. acnes, sebum